Effect of Articular Needling Therapy Combined with Proprioceptive Training on Patients with Knee Osteoarthritis - CHEN He; LI Xuemei; KUANG Xuehui; YU Jin (康复学报)
ObjectiveTo observe the clinical effect of articular needling therapy combined with proprioceptive training on patients with knee osteoarthritis (KOA).MethodsA total of 90 KOA patients in the Foshan Traditional Chinese Medicine Hospital Affiliated to Guangzhou University of Medicine from February 2021 to October 2022 were randomly divided into control group and observation group, with 45 cases in each group. The control group received routine treatments such as stretching therapy, joint loosening, muscle strength training and intermediate frequency therapy, with each treatment was 10 minutes a time, once a day, six days a week, lasting for four weeks. The observation group received articular needling therapy combined with proprioceptive training on the basis of the control group, articular needling therapy was performed 20 minutes a time, once a day, six days a week, lasting for four weeks; proprioception training was performed 10 minutes a time, once a day, six days a week, lasting for four weeks. Before and after treatment, visual analog scale (VAS) score was used to evaluate the pain degree of knee joint; Western Ontario and McMaster University osteoarthritis index (WOMAC) was used to evaluate knee joint function; average trajectory error of the affected limb and Berg balance scale (BBS) score was used to evaluate balance function of lower limb.ResultsCompared with that before treatment, VAS score, WOMAC and average trajectory error of the affected limb of the both groups after treatment decreased significantly, while BBS score increased significantly, the difference was statistically significant(P<0.05). Compared with the control group, VAS score, WOMAC and average trajectory error of the affected limb of the observation group after treatment were lower, while BBS score was significantly higher, the difference was statistically significant (P<0.05).ConclusionsArticular needling therapy combined with proprioceptive training can effectively improve pain of knee joint, knee joint function, and balance function of lower limb of KOA patients.